论新加坡电影的俚语字幕翻译策略 = Subtitle translation of Slangs in Singapore films : a study on translation strategies - 江莉妏 Kang, Lye Boon (2016)
新加坡当代电影几乎都使用新加坡式的混合语，融汇了华语、英语、马来语、淡米尔语和华语方言等，体现了新加坡多元种族／多语言的特征。俚语便在此语言环境下产生。但是，若电影中使用大量的俚语，不时会造成外国人理解内容和对白的障碍。为了让更多外国观众能接受和欣赏新加坡本土电影，字幕翻译成了观众和电影之间必不可少的桥梁。此外，影视字幕翻译需在限定的时间和空间内，言简意赅地传达最贴切的信息。本文将以新加坡著名导演梁智强于 1998 至 2015 年的四部电影为研究案例，分析当中的俚语字幕翻策略是否有效传递与原文意义对等的信息。Singapore’s unique blend of language, which comprises of Mandarin, English, Malay, Tamil and Chinese dialects et cetera are seen in almost every local film, which portrays the multi racial and multi language society of Singapore. Slangs are developed under this multi language environment, and they are commonly used in local films to enhance the local touch. However, excessive use of such colloquial language would cause non-Singaporean audiences to have a difficult time to comprehend. Furthermore, subtitle translation allows understanding and it is an important factor for non-Singaporeans to be able to appreciate local films. Subtitle translation face two constrains - space and time. Hence, subtitles are to be condensed and convey the apt information. This dissertation will use 4 movies between 1998-2015 by Singapore renowned filmmaker Jack Neo as case studies. The translation strategies used in subtitling of slangs in the films will be studied, and examine if they are able to convey equivalent information of the source language.